All-trans retinoic acid suppresses the adhering ability of ARPE-19 cells via mitogen-activated protein kinase and focal adhesion kinase - Yo-Chen Chang; Yuh-Shin Chang; Ming-Chu Hsieh; Horng-Jiun Wu; Meng-Hsien Wu; Chia-Wei Lin; Wen-Chuan Wu; Ying-Hsien Kao (Elsevier, 2016)
This study investigated the signaling mechanism underlying the anti-adhesive effect of all-trans retinoic acid (ATRA) on retinal pigment epithelial ARPE-19 cells. Adhesion kinetics with or without ATRA treatment were profiled by adhesion assay. Surface coating with type IV collagen, fibronectin, laminin, but not type I collagen, significantly enhanced adhesion and spreading of ARPE-19 cells, while ATRA at subtoxic doses (ranging from 10-7 to 10-6 M) profoundly suppressed the extracellular matrix-enhanced adhesion ability. Cell attachment on FN activated PI3K/Akt and MAPK cascades, whereas ATRA pretreatment blunted the early phosphorylation of Akt and MAPK signaling mediators including p38 MAPK, JNK1/2, and ERK1/2. Mechanistically, signaling blockade with selective kinase inhibitors demonstrated that all MAPK pathways were involved in the anti-adhesive effect of ATRA, whereas the PI3K inhibitor treatment significantly potentiated the ATRA-suppressed RPE cell adhesion. Moreover, ATRA treatment did not affect intracellular F-actin distribution, but remarkably reduced focal adhesion kinase (FAK) expression and its nuclear localization during ARPE-19 cell attachment. In conclusion, ATRA suppresses the adhering ability of ARPE-19 cells at least in part through MAPK and FAK pathways. Signaling blockade with PI3K inhibitor could be regarded as an alternative modality for treating proliferative vitreoretinopathy.